Comparative assessment of effectiveness of alternative genotyping assays for characterizing carotenoids accumulation in tropical maize inbred lines - Sayadi Maazou, A.R.; Gedil, Melaku A; Adetimirin, Victor O.; Meseka, S.K.; Mengesha Abera, W.; Babalola, D.; Offornedo, Q.N.; Menkir, A. (MDPI, 2021)
The development of maize varieties with increased concentration of Provitamin A (PVA) is an effective and affordable strategy to combat vitamin A deficiency in developing nations. However, the considerably high cost of carotene analysis poses a major challenge for maize PVA biofortification, prompting the use of marker-assisted selection. Presently, two types of genotyping with PVA trait-linked functional markers have been developed and extensively used in breeding programs. The two systems are low throughput gel-based genotyping and genotyping with Kompetitive Allele-Specific PCR (KASP) single nucleotide polymorphism (SNPs) markers. Although the KASP SNPs genotyping was developed to replace the gel-based genotyping, studies have not been conducted to compare the effectiveness of the KASP SNPs markers with the gel-based markers. This study was conducted to assess the carotenoid content of 64 tropical PVA biofortified maize inbred lines containing temperate germplasm in their genetic backgrounds and screen them with both gel-based and KASP markers of PSY1, LCYE and crtRB1 genes. Many of the 64 inbred lines had PVA concentrations surpassing the 15 µg/g provitamin A breeding target set by the HarvestPlus Challenge Program. Favorable alleles of crtRB1, crtRB1 and the KASP SNPs markers were detected in 25 inbred lines with high PVA concentrations. Inbred lines with the favorable alleles of LCYE had the highest concentrations of non-PVA carotenoids, whereas those with the favorable alleles of crtRB1 had high levels of PVA carotenoids. Data from the sequenced region of LCYE revealed one SNP in the first intron that clearly differentiated the high and low β-carotene maize inbred lines. The results of our study demonstrate that the automated KASP SNPs markers can replace the gel-based genotyping for screening a large number of early generation maize inbred lines for PVA content.